Respon Pertumbuhan Dan Hasil Tanaman Sawi (Brassica Sp.) Terhadap Komposisi Media Tanam Dan Penyiraman Air Kolam Bioflok Lele Dalam Polibag - Aziz, Abdul; Sunaryo, Yacobus; Darnawi (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of the study was to determine the effect of the composition of the growing media and the effect of providing a biofloc pond on the growth and yield of mustard plants. The research was carried out under the auspices of a plastic house on a yard in Krikilan Hamlet, Tegalterto Village, Berbah District, Sleman Regency,Special Region of Yogyakarta, at an altitude of ± 194 masl. The average rainfall is 2500 - 3000 mm per year and has a temperature between 38°C to 39°C in the shade. The study was carried out from December 2021 to January 2022. This study used an experiment with a 2 x 2 x 2 factorial completely randomized design (CRD). The first factor was the type of mustard greens consisting of 2 levels: caisim (S1) and pakcoy (S2). The second factor was the composition of the growing media which consisted of 2 levels: soil + husk charcoal (M1) and soil + husk charcoal + bokasi (M2). The third factor is watering the catfish biofloc pond water which consists of two levels I1 (without watering the biofloc pond water with NPK fertilization) and I2 (watering the biofloc catfish pond every 2 days).data used analysis of variance to determine the effect of treatment on the variables, followed by DMRT (Duncan Multiple Range Test). The results showed that there was no interaction between the type of mustard greens, the composition of the planting medium, and watering of the catfish biofloc pond, but there was an interaction between the type of mustard and the media on the stem diameter and dry weight of the plant, and there was an interaction between the type of mustard and the watering of the biofloc water on the plant height, width and width. leaf length, leaf length, and root length. Caisim (S1) treatment which was grown on soil + husk charcoal (M1) growing media composition and without watering the catfish biofloc pond water with NPK (I1) fertilization could increase the growth and yield of mustard plants better than other combination treatments